63+-x=2x+3

Simple and best practice solution for 63+-x=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63+-x=2x+3 equation:


Simplifying
63 + -1x = 2x + 3

Reorder the terms:
63 + -1x = 3 + 2x

Solving
63 + -1x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
63 + -1x + -2x = 3 + 2x + -2x

Combine like terms: -1x + -2x = -3x
63 + -3x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
63 + -3x = 3 + 0
63 + -3x = 3

Add '-63' to each side of the equation.
63 + -63 + -3x = 3 + -63

Combine like terms: 63 + -63 = 0
0 + -3x = 3 + -63
-3x = 3 + -63

Combine like terms: 3 + -63 = -60
-3x = -60

Divide each side by '-3'.
x = 20

Simplifying
x = 20

See similar equations:

| JOSE+JOSE= | | 7y+7=7y+8 | | 3+65x=39x+9 | | a=(.5x+1)x^2+8x+12 | | .03(x)-.09(y)=14000 | | 5(2c-3)=7 | | a^2+2abi-b^2=8+6i | | 6x-1=15x-26 | | 11z=-33+8z | | 4t=2t-10 | | C=a+8 | | y=3x^4-6x^2+3 | | =31/2*(1-3)^4 | | 12.31+0.07x=12.81+0.08x | | X+8=4X+3+229 | | x/12-3=5/24 | | -12X+14=-24 | | (-5+3i)(4+7i)= | | 39+-12w=7+-16w | | 180-i=(i-56) | | k-9.5=10 | | 15+5z=10 | | k-9.5=10whatisk | | 1/-12÷2/3 | | 0.7x+3.1=0.6x+1.6 | | tn-1=tn-1+2 | | Y-1=9y-9 | | y+8+15=2 | | 5x+8y=23 | | 2x=5.67 | | 16a=25*64 | | 3.6x-24=2.1x+9 |

Equations solver categories